Synthesis and characterization of a new cyclobutane substituted Schiff base ligand and its Cd(II), Co(II), Ni(II) and Zn(II) complexes - Cukurovali, A; Yilmaz, I (Polish Chemical Society, 2000)
[Abstract Not Available]
Keywords: Derivatives